Migrants and citizens : demographic change in the European state system - Koslowski, Rey. (Ithaca, NY : Cornell University Press, 2000)
The Berlin Wall falls as thousands of East Germans move to the West; after the Iron Curtain lifts, West Europeans brace for mass migrations from Eastern Europe; millions of refugees flee Iraq, Bosnia, Haiti, Rwanda, and other strife-torn nations. The ...
Cover; Migrants and Citizens; Title; Copyright; Dedication; Contents; Acknowledgments; Introduction; PART 1 Theoretical Issues; 1 Migration and the Conceptualization of World Politics; 2 European Integration and State Sovereignty; PART 2 Demography Shaping Political Institutions; 3 Nation-States; 4 Citizenship; 5 Political Union; PART 3 Migration, Citizenship, and the Emerging European Polity; 6 European Union Citizenship; 7 Dual Nationality; 8 Border Control and State Sovereignty; Conclusion; Notes; References; Index
Includes bibliographical references (pages 201-223) and index.
JSTOR
Keywords: Europe -- Emigration and immigration; Europe -- Emigration and immigration -- Government policy; Europe -- Émigration et immigration; Europe -- Émigration et immigration -- Politique gouvernementale; SOCIAL SCIENCE -- Emigration & Immigration; Emigration and immigration; Emigration and immigration -- Government policy; Europe; Migratie (demografie); Migratiebeleid; Overheidsbeleid